Optimization of ethanol production from mango peels using response surface methodology - Abdul Ghani, M.R. (Trans Tech Publications Ltd, 2014)
This study aims to optimize bioethanol production from mango peels using Response Surface Methodology (RSM). The effect of temperature (25â40oC), yeast concentration (6â14 g/ml) and fermentation time (48â96 hours) on bioethanol yield was investigated. Prior to the fermentation process, mango peels were treated with 0.25â1 (w/v) sulphuric acid. Optimum glucose yield was obtained at 0.25 (w/v) sulphuric acid. RSM using 3-factor 2-level central composite design (CCD) was employed to evaluate and optimize the synthesis parameters. Based on numerical optimization, the optimum fermentation conditions were at 38oC using 6 g/ml yeast for 48 hours, giving a yield of 7.34 g/ml bioethanol. Â© 2014 Trans Tech Publications, Switzerland.